Anatomical structure of the wood of two oaks from Oaxaca, Mexico - Ruiz-Aquino, Faustino; González-Peña, Marcos M.; Valdez-Hernández, Juan I.; Romero-Manzanares, Angélica (Instituto de Ecología, A.C., 2016)
Mexico is a distribution center for the genus Quercus, with 161 species recorded; some 60 of these have favorable characteristics for lumber usage. Herein, we describe the anatomical characteristics of Quercus crassifolia and Q. laurina wood, and these characteristics are correlated with wood basic density, volumetric shrinkage, and hardness. Quercus laurina wood displayed high brightness and medium grain, while in Q. crassifolia these were medium and coarse, respectively. Wood from both species was ring-porous, with solitary oval pores; parenchyma was apotracheal diffuse-in-aggregates, and there were uniseriate, multiseriate and aggregate rays, as well as libriform fibers and fibrotracheids. In Q. laurina, strong correlations were found between the fiber wall thickness and basic density (r = 0,97), and between the lumen diameter and volumetric shrinkage (r > 0,99); while in Q. crassifolia the strongest correlations occurred between the volumetric shrinkage and both the fiber wall thickness (r = 0,97), and the fiber diameter (r = 0,93). In both oaks, a high volumetric shrinkage and the presence of very broad rays, indicate a high propensity of wood to develop cracks and splits upon drying.